2005
DOI: 10.1002/ptr.1443
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects of daucane esters from Ferula communis and F. arrigonii on human colon cancer cell lines

Abstract: Certain jaesekanadiol p-hydroxy- and p-methoxybenzoates - typical of Ferula communis and Ferula arrigonii sardinian plants - show antiproliferative activity on human colon cancer less. The inhibitory doses 50%, calculated after 72 h of treatment, revealed that the antiproliferative capacity of the compounds was in the following descending order: ferutinin > 2alpha-OH-ferutidin > ferutidin > siol anisate > lapiferin > jaeskeanadiol. Evidence is presented that interaction with type II estrogen-binding sites (EBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 17 publications
6
47
0
Order By: Relevance
“…2, DE-17 induced, in a concentration-dependent manner, a G1 arrest along with a decrease of the S phase, whereas the G2/M remain practically unchanged. These results are in agreement with that of Poli et al (2005) which reported that daucane esters induced antiproliferative activity in three colon cancer cell lines and this effect was preceded by cell cycle arrest in the G1 phase. In this context it is also worthwhile to note that our previous work (Dall'Acqua et al, 2011) indicates that other daucane esters may induce a cell cycle arrest in G1 or in G2/M phase depending on the different structure.…”
Section: Compound De-17 Induced Cell Cycle Arrest In G1 Phasesupporting
confidence: 95%
“…2, DE-17 induced, in a concentration-dependent manner, a G1 arrest along with a decrease of the S phase, whereas the G2/M remain practically unchanged. These results are in agreement with that of Poli et al (2005) which reported that daucane esters induced antiproliferative activity in three colon cancer cell lines and this effect was preceded by cell cycle arrest in the G1 phase. In this context it is also worthwhile to note that our previous work (Dall'Acqua et al, 2011) indicates that other daucane esters may induce a cell cycle arrest in G1 or in G2/M phase depending on the different structure.…”
Section: Compound De-17 Induced Cell Cycle Arrest In G1 Phasesupporting
confidence: 95%
“…Endemic taxa are very interesting because the geographic isolation has been caused a genetic and metabolic differentiation in these species, as shown by the high number of scientific researches that have been published until now (Fattorusso et al, 2004;Petitto et al, 2009;Ramunno et al, 2005;Serrilli et al, 2005Serrilli et al, , 2010. Some of Sardinian endemism have also shown very interesting biological and pharmacological activities Calzado et al, 2005;Poli et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…In an earlier report, lapiferin was purified from the roots of F. lapidosa and its structure and configuration have been established on the basis of chemical transformations and the analysis of spectral characteristics (Diaz, Fragam, Gonzala`z, Gonzala`z, & Hernandez, 1984;Golovina, Saidkhodzhaev, Abdullaev, Malikov, & Yagudaev, 1983). Recently, lapiferin extracted from F. communis and F. arrigonii sardinian showed antiproliferative activity against human colon cancer, and the interaction with type II estrogen-binding sites underlies this activity (Poli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%